Policy Options for Poverty Alleviation - Miguel Székely (Inter-American Development Bank, Office of the Chief Economist, 1997)
This work builds on previous research to develop a methodology that simplifies the identification of the best policy options for poverty alleviation in a given country. When a population can be divided into subgroups according to an easily identifiable characteristic, the problem of alleviating poverty through a targeted mechanism can be viewed as one of choosing of three options: (i) provoking a marginal change in the average income of certain subgroups; (ii) changing the resource distribution within marginal subgroups; and (iii) generating a marginal change in the differences between the subgroups. Recent data from Mexico is applied.
Keywords: 330